Vegetative Propagation of Red Sanders (Pterocarpus santalinus Linn.) - Kesava Reddy, K.; Srivasuki, K. P. (Indian Forester, 1990)
Ptrocarpus sanlalinus an endemic species to the region of Cuddapah geological formation is highly valued due to its export potential to Japan. The choice of the Japanese is for its sound wavy grained logs. The forest department of Andhra Pradesh tried for propagation of the species vegetatively by means of rooted cuttings, air layering and grafting. The present paper analyses the grafting, air layering and rooting experiment conducted in the past. The results indicate that the technique of grafting has limited scope in large scale propagation of the species. Similarly air layering has got its own limitations and requires further standardisation. Rooting of cuttings offers great scope in propogating the elite trees on a large scale vegetatively. For propagation of the species by adopting tissue culture technology has great potential and efforts are also on way to utilise this technique for establishing clonal seed orchards in Andhra Pradesh.